Different synchronization schemes for chaotic Rikitake systems - Ali Khan, Mohammad (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents the chaos synchronization by designing a different type of controllers. Firstly, we propose the synchronization of bi-directional coupled chaotic Rikitake systems via hybrid feedback control. Secondly, we study the synchronization of unidirectionally coupled Rikitake systems using hybrid feedback control. Lastly, we investigate the synchronization of unidirectionally coupled Rikitake chaotic systems using tracking control. Comparing all the results, finally, we conclude that tracking control is more effective than feedback control. Simulation results are presented to show the efficiency of synchronization schemes.
Keywords: chaotic system; chaos synchronization; chaos control; Rikitake system